Promoting Behavioral Support for Change: A Conservation of Resources Theory Perspective - Mehboob, Farhan; Othman, Noraini (SEISENSE (PRIVATE) LIMITED, 2020)
Purpose- Individuals' support for change is a critical success factor to implement change effectively. Therefore, identifying the possible antecedent and mechanism, leading to behavioral support towards change, is necessary. The study aims to unfold this avenue of research empirically by examining the role of both person and context factors in promoting behavioral support for change. Design/Methodology- Data was collected from 292 academic staff of six public sector universities located in Pakistan via cross-sectional mean. A self-reported questionnaire was used to collect responses from the desired population. Findings- Results revealed a positive impact of perceived management support on academic staff’s behavioral support for change. Moreover, change-efficacy also provides a statistically significant intervening mechanism to translate the effect of perceived management support on both dimensions of behavioral support to change such as compliance and championing behavior Practical Implications- The research offers useful insights for top university officials to build support for change by providing needed support and resources; make academic staff capable of executing the change-related tasks into viable actions meritoriously.